2016
DOI: 10.1111/iwj.12680
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for ulceration over tophi in patients with gout

Abstract: Ulceration over tophi in patients with gout usually causes a number of clinical problems. The aim of this study was to investigate the risk factors for ulceration of tophi in patients with gout. Patients with gout who had tophi with or without ulceration were prospectively recruited and underwent a comprehensive clinical assessment. Clinical factors independently associated with the presence of ulceration were analysed using logistic regression models. Of the 113 participants, 18 (13·7%) had clinically apparen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…However, our finding suggested that serum urate, gout duration and GFR were not risk factors for tophi ulceration. This is in accordance with the previous study . Meanwhile, our study also did not demonstrated age as an independent risk factor for ulceration over tophi, which was not consistent with the previous study, although patients with ulcerations were older in our study.…”
Section: Discussionsupporting
confidence: 80%
“…However, our finding suggested that serum urate, gout duration and GFR were not risk factors for tophi ulceration. This is in accordance with the previous study . Meanwhile, our study also did not demonstrated age as an independent risk factor for ulceration over tophi, which was not consistent with the previous study, although patients with ulcerations were older in our study.…”
Section: Discussionsupporting
confidence: 80%
“… 16 , 17 In our recent study of risk factors for ulceration over tophi in patients with gout, 77.8% of 113 patients had ulceration on the foot, and friction was the major cause of tophi ulceration. 21 In the present study, patients with infection had a significantly longer ulcer duration and larger ulcer size than those without infection, indicating that both a longer ulcer duration and larger ulcer size may be risk factors for infectious ulceration over tophi in patients with gout.…”
Section: Discussionsupporting
confidence: 45%
“…They found that 13.7% of the patients in this population had clinically apparent ulceration over the tophus, 78% of which were located on the feet. The study also found that ulceration of tophi was independently correlated with older age, increased size of tophi, and a lack of protective sensation [5].…”
mentioning
confidence: 61%